1998
DOI: 10.1016/s0378-1097(97)00494-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an endo-1,4-β-mannanase from Bacillus subtilis KU-1

Abstract: Endo-1,4-L-mannanase was purified to homogeneity from the culture supernatant of Bacillus subtilis KU-1 by ammonium sulfate precipitation, DEAE-Toyopearl, phenyl-Sepharose and FPLC Mono Q column chromatography by 810-fold with 39% yield. The molecular mass of the enzyme was estimated to be 39 kDa by SDS-PAGE and 40 kDa by gel filtration. It had a pI of 4.5 with maximum activity at pH 7.0 and 50^55³C. It was stable for 48 h between pH 4.5 and 9.0, and for 1 h up to 60³C. The enzyme activity was strongly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…The specific activity of Man26P (514 U mg -1 ) is higher than that of MANB48 from Bacillus circulans strain K-1 (481.55 U mg -1 ) (Li et al 2008), MAN5C from Paecilomyces lilacinus (14.5 U mg -1 ) (Sugino et al 2004), Man26A from Bacillus sp. strain JAMB-750 (36.3 U mg -1 ) (Hatada et al 2005) and the b-mannanase from Bacillus subtilis KU-1 (407.7 U mg -1 ) (Zakakaria and Yagi 1998). It is similar that of Man26B from Clostridium thermocellum (520 U mg -1 ) (Kurokawa et al 2001), but lower than that of the b-mannanase from Streptomyces lividans 66 (876 U mg -1 ) (Arcand et al 1993) or ManA from alkaliphilic Bacillus sp.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The specific activity of Man26P (514 U mg -1 ) is higher than that of MANB48 from Bacillus circulans strain K-1 (481.55 U mg -1 ) (Li et al 2008), MAN5C from Paecilomyces lilacinus (14.5 U mg -1 ) (Sugino et al 2004), Man26A from Bacillus sp. strain JAMB-750 (36.3 U mg -1 ) (Hatada et al 2005) and the b-mannanase from Bacillus subtilis KU-1 (407.7 U mg -1 ) (Zakakaria and Yagi 1998). It is similar that of Man26B from Clostridium thermocellum (520 U mg -1 ) (Kurokawa et al 2001), but lower than that of the b-mannanase from Streptomyces lividans 66 (876 U mg -1 ) (Arcand et al 1993) or ManA from alkaliphilic Bacillus sp.…”
Section: Discussionmentioning
confidence: 90%
“…Cu 2? has been shown to inhibit some mannanases (Zakakaria and Yagi 1998;Tamaru et al 1995). EDTA showed negative effects on the activity of Man26P, which indicates that it does not require divalent ions to function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus spp. mannanases have a molecular mass in the range of 37-40 kDa [20][21][22] . Nevertheless, Takeda et al 23 reported that the purified mannanase from Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Mannanases are produced mainly by members of the genus Bacillus. Bacillus subtilis is recommended because of its safety, fast growth, and ability to secrete high levels of mannanase into the medium (Khanongnuch et al 1998;Zakaria et al 1998;Jiang et al 2006;Dhawan and Kaur 2007). Despite having high practical potential, the use of mannanase is still limited, due to low yields and high production costs (Dhawan and Kaur 2007;Zhang et al 2000).…”
Section: Introductionmentioning
confidence: 99%